EFEKTIVITAS KEGIATAN LITERASI DIGITAL DALAM MENINGKATKAN KEMAMPUAN PENULISAN KARYA ILMIAH BAGI MAHASISWA - Maryatun Maryatun (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
The concept of literacy has been widely used more widely in various fields. The form of literacy activities can be packaged as a soft skills development activity. Training on using Microsoft Word and reference management tools is one of the mandatory activities for students of the Faculty of Economics and Business, Gadjah Mada University, 2017/2018. This study wants to know the effectiveness of literacy activities in improving the ability to write scientific papers for students. The research method uses quantitative descriptive method with the type of evaluation research. The research sample was 245 students who were active in the regular undergraduate study program and the International Undergraduate Program. The result of his research is that literacy activities in the form of microsoft word training and reference management tools are effective in improving students' scientific writing skills. This is indicated by the score above 3 on the variable of speaker, material, and training infrastructure, while the training atmosphere variable scores score less than 3, which means it is not boring and interesting.